Analysis of HRM Impact on Organizational Performance of Trading Sector Public Enterprises in Nepal - Panthi, Rishikesh (The Management Review, 2026)
This study aims to provide a comprehensive analysis of the contribution of Human Resource Management to the effectiveness, efficiency, and overall performance of Nepalese trading sector public enterprises. The study is based on a combination of both descriptive and causal-comparative research designs to achieve its objectives. Descriptive research design is used to describe the different phenomenon of the dependent and independent variables. Similarly, the casual comparative research design is used to examine the magnitude of impact of independent variables on dependent variable. The data have been collected through the 5-points Likert scale structured questionnaires from the 134 out of 196 respondents including officer level employees of 5 trading sector public enterprises by stratified random sampling method and some key informants were interviewed. The regression results confirmed that human resource management has the significant positive impact on organizational performance of trading sector public enterprises in Nepal. The findings of the study reveal that the performance level of trading sector public enterprises was below satisfactory standards, primarily due to ineffective human resource management practices within public enterprises. The study provides valuable insights for the Government of Nepal, concerned authorities, stakeholders, employees, executives of public enterprises, policymakers, researchers, academicians, and experts, serving as a significant reference for further research and policy formulation in this field.